Attitudes to conserving biodiversity and the experienced possibilities and challenges A case study with individual forest owners in Sweden - Amann, Katrin; Eberger, Jenny (My University, 2022)
Forests provide welfare to Sweden in many aspects, but the national goals for biodiversity conservation in these forests are not met. Individual forest owners are part of the solution, as they have the power to manage their land. The purpose with the case study was to investigate individual forest owners’ attitudes to biodiversity conservation in forestry and their perceived possibilities and challenges. A qualitative method was used with semi-structured interviews together with a literature search. The interviews were done with 30 individual Swedish forest owners, owning five to more than a thousand hectares. A conceptual framework was used to understand preconditions for behavioural change to solve environmental problems. The three most frequently mentioned possibilities were: taking general nature considerations in forestry, using continuous cover forestry (CCF) methods, and small-scale forestry as it is seen as an enabler for biodiversity. The three most frequently mentioned challenges were: lack of profitability when enhancing biodiversity, damage from elk and deer, and being afraid of having too much biodiversity. More than half of the forest owners believe biodiversity conservation is important. Most forest owners are willing to use CCF methods, to a varied degree, but experience difficulties to implement these. Only a few think that laws, regulations, and certifications work well for biodiversity conservation in Sweden, and the majority are afraid of losing ownership rights if authorities find high levels of biodiversity in their forests. There might be a potential to strengthen the acceptance of structural measures for biodiversity conservation, such as regulations, if more respect is paid to individual forest owners’ attitudes.
Keywords: Biodiversity; Forest; Forestry; Forest owner; Sweden; Sustainable forests; Possibilities; Challenges; Attitudes